The Use of Engage, Research, Activate (ESA) Method to Enhance Students’ Ability in Writing Descriptive Text - Firman Rustam (Lingedu: Journal of Linguistics and Education, 2025)
The research explores the effectiveness of the Engage, Study, Activate (ESA) method in enhancing the writing ability of first- year students at SMA Yapip Sungguminasa, particularly in producing descriptive texts. A pre-experimental design was employed, utilizing pre-tests and post-tests. The population of the study consisted of 110 first-grade students from SMA Yapip Sungguminasa during the 2013/2014 academic year. A purposive sampling technique was employed to select one class (X.A) consisting of 30 students with low writing achievement. The instrument used for data collection was a written test, where students were required to write descriptive texts based on provided images. The same type of test was used for both the pre- test and post-test evaluations. The results demonstrated a significant improvement in students' writing performance, particularly in content and organization. These findings suggest that the ESA method effectively fosters student engagement, linguistic awareness, and active language use, leading to more coherent and complete descriptive writing.